77.7k views
4 votes
Find p(-3) and p(5) for the function p(x) = 2x⁴ + 3x³ - 9x² + 16x + 13.​

User JDB
by
5.2k points

1 Answer

3 votes

Answer:

-35, 1493

Explanation:

p(x) = 2x⁴ + 3x³ - 9x² + 16x + 13

p(-3) = 2(-3⁴) + 3(-3³) - 9(-3²) + 16(-3) + 13

-3² = 9

-3³ = -27

-3⁴ = 81

p(-3) = 2(81) + 3(-27) -9(9) - 48 + 13

p(-3) = 162 - 81 - 81 -48 + 13

81 + 81 = 162 therefore 162 - 81 - 81 cancels

-48 + 13 = -35

p(5) = 2(5⁴) + 3(5³) - 9(5²) + 16(5) + 13

5² = 25

5³ = 125

5⁴ = 625

p(5) = 2(625) + 3(125) - 9(25) + 80 + 13

p(5) = 1250 + 375 - 225 + 93

p(5) = 1250 + 150 + 93

p(5) = 1493

User The Hoff
by
5.2k points